Drought Stress Mitigating Morphological, Physiological, Biochemical, and Molecular Responses of Guava (Psidium guajava L.) Cultivars - Usman, Muhammad; Bokhari, Syeda Anum Masood; Fatima, Bilquees; Rashid, Bushra; Nadeem, Faisal; Sarwar, Muhammad Bilal; Nawaz-ul-Rehman, Muhammad Shah; Shahid, Muhammad; Ayub, Chaudhary Muhammad (Frontiers in Plant Science, 2022)
Guava (Psidium guajava L.), a major fruit crop of the sub-tropical region, is facing production decline due to drought stress. Morphophysiological responses to drought stress and underlying transcriptional regulations in guava are, largely, unknown. This study evaluated the drought stress tolerance of two guava cultivars, viz. “Gola” and “Surahi”, at morphological and physiological levels regulated differentially by ESTs (Expressed Sequence Tags). The treatments comprised of three moisture regimes viz. To = 100% (control), T1 = 75% and T2 = 50% of field capacity. There was an overall decrease in both morphological and physiological attributes of studied guava cultivars in response to drought stress. Nonetheless, water use efficiency of “Surahi” cultivar increased (41.86%) speculating its higher drought tolerance based on enhanced peroxidase (402%) and catalase (170.21%) activities under 50% field capacity (T2). Moreover, higher proline and flavonoid contents reinforced drought stress retaliation of “Surahi” cultivar. The differential expression of a significant number of ESTs in “Surahi” (234) as compared to “Gola” (117) cultivar, somehow, regulated its cellular, biological and molecular functions to strengthen morpho-physiological attributes against drought stress as indicated by the up-regulation of ESTs related to peroxidase, sucrose synthase (SUS), alcohol dehydrogenase (ADH) and ubiquitin at morphological, biochemical and physiological levels. In conclusion, the drought stress acclimation of pear-shaped guava cultivar “Surahi” is due to the increased activities of peroxidase (POD) and catalase (CAT) complimented by the upregulation of related ESTs.